Factors influencing breastfeeding for working mothers - Yılmaz, Gonca; Gürakan, Berkan; Akgün, Seval; Özbek, Namık (The Turkish Journal of Pediatrics, 2002)
In order to evaluate the relation between breastfeeding and working conditions a descriptive study was conducted on 301 working mothers. Seventy-seven percent of mothers breastfed their infants four months and longer, and the mean breastfeeding period was 6.2 ± 3.4 months. Forty-one percent of mothers started weaning before four months of age. The multifactorial analysis of independent factors significantly influencing breastfeeding time were, in decreasing order of significance, breastfeeding conditions at work, maternal leave period, mother’s smoking habit and the use of breastpump. For weaning period, these factors were the use of breastpump, breastfeeding leave at work and maternal leave period. In conclusion, in order to support breastfeeding at work, maternal leave period must be prolonged, and breastfeeding conditions at work must be improved.